2017
DOI: 10.1136/eb-2017-102782
|View full text |Cite
|
Sign up to set email alerts
|

Critical care nursing: caring for patients who are agitated

Abstract: This month's opinion draws on an EBN Twitter chat that focused on caring for patients who are agitated. Access the blog at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The use of subjective descriptors further emphasises the lack of objective clinical guidance for staff caring for agitated or delirious patients. It is difficult to quantify at what point the use of restraint becomes clinically necessary (Freeman & Teece, ). Hurlock‐Chorostecki and Kielb () demonstrated how education and culture change reduced reliance on physical restraints on their unit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of subjective descriptors further emphasises the lack of objective clinical guidance for staff caring for agitated or delirious patients. It is difficult to quantify at what point the use of restraint becomes clinically necessary (Freeman & Teece, ). Hurlock‐Chorostecki and Kielb () demonstrated how education and culture change reduced reliance on physical restraints on their unit.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical and physical restraint are widespread in critical care, and bedside nurses are the main decision-makers in restraint management (Li & Fawcett, 2014). However, agitation can be subjectively interpreted, leading to challenges in identifying the point at which restraint becomes appropriate (Freeman & Teece, 2017) and subsequent wide variations in practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…53 To improve patient outcomes, written physician orders, family-co-ordinated multidisciplinary decision-making with psychiatric support, and tools indicating the determinants for clinical use of PR and delirium scoring are needed. 54 In this study, nurses identified workload as one reason for not using alternatives to PR. Compared with other studies, the nurse-topatient ratio is very low in Turkey.…”
Section: Nurses' Demographic and Professional Factorsmentioning
confidence: 99%